Diffusion of hydrous species in model basaltic melt. (15th October 2017) - Zhang, Li; Guo, Xuan; Wang, Qinxia; Ding, Jiale; Ni, Huaiwei
Abstract: Water diffusion in Fe-free model basaltic melt with up to 2 wt% H2 O was investigated at 1658–1846 K and 1 GPa in piston-cylinder apparatus using both hydration and diffusion couple techniques. Diffusion profiles measured by FTIR are consistent with a model in which both molecular H2 O (H2 O m ) and hydroxyl (OH) contribute to water diffusion. OH diffusivity is roughly 13% of H2 O m diffusivity, showing little dependence on temperature or water concentration. Water diffusion is dominated by the motion of OH until total H2 O (H2 O t ) concentration reaches 1 wt%. The dependence of apparent H2 O t diffusivity on H2 O t concentration appears to be overestimated by a previous study on MORB melt, but H2 O t diffusivity at 1 wt% H2 O t in basaltic melt is still greater than those in rhyolitic to andesitic melts. The appreciable contribution of OH to water diffusion in basaltic melt can be explained by enhanced mobility of OH, probably associated with the development of free hydroxyl bonded with network-modifying cations, as well as higher OH concentration. Calculation based on the Nernst-Einstein equation demonstrates that OH may serve as an effective charge carrier in hydrous basaltic melt, which could partly account for the previously observed strong influence of water on electrical conductivity of basaltic melt.